Mercury (II) removal using CNTS grown on GACs - Kabbashi, Nassereldeen; Mirghani, Mohamed Elwathig Saeed; Salleh, N. W. (2011)
Elemental (metallic) mercury primarily causes health effects when it is breathed as a vapor where it can be absorbed through the lungs, at higher exposures there may be kidney effects, respiratory failure and death. This study aimed to study the performance of carbon nanotubes (CNT) grown on granular activated carbon (GAC) as an adsorbent for removal of mercury from aqueous solution. Due to its highly toxic effects to humans and environment, heavy metal concentrations in water are restricted by strict standards and reduced to the standard permitted. The effect of pH, agitation speed,contact time and CNT dosage was studied for optimal adsorption of mercury in the aqueous solution. Design Expert software was used to determine the number of runs and its variations,which are 18 runs. It was found that the optimal condition for mercury (II) ions adsorption occurred at adsorbent dosage of 5 mg, pH value of 5, contact time of 120 minutes and agitation speed of 150 rpm. The model resulted R2= 0.8517 indicating 85.17% of the factors,which were pH, contact time,agitation speed and adsorbent dosage correlated to each other.